(untitled) (World Economics and Finance Bulletin, 2023)
The development of investment tools and economic institutions, the urgent need for customers and beneficiaries, global and local developments, and the superiority and development of accounting systems have led to the availability of high-quality information for all internal and external parties. Accounting is considered a stand-alone system with its own inputs, which it relies on in the accounting registration process and in preparing the outputs of this system, represented by financial statements. The reasons for choosing the topic were its importance in professional life, its novelty, and the lack of studies in it. Financial statements represent a complete set of accounting and financial documents that cannot be separated from each other, and allow for an accurate picture of the financial position of the institution when closing accounts. The importance of financial statements lies in their role as a communication tool, a means of evaluating performance, and a means of making necessary decisions. The financial accounting system specifies an integrated set of financial statements that all accounting units must prepare periodically, including the balance sheet, income statement, cash flow statement, statement of changes in equity, and the appendix of accounting rules and methods used in preparing the aforementioned statements. The objectives of financial statements and their characteristics are to provide appropriate information for performance evaluation, etc. The qualitative characteristics of financial statements include understandability, relevance, reliability, and comparability. The factors that affect financial statements are the type of economic system, the impact of professional organizations and regulatory bodies on the securities market, government intervention, inflation, and rising prices. The purpose of this study is to highlight aspects related to financial statements, including their importance, components, objectives, typical characteristics, and technical aspects of the subject.